Otimização de uma classe de benzenossulfonamidas como agentes anti-trypanosomatidae: planejamento, síntese e avaliação biológica contra Trypanosoma cruzi e Leishmania infantum - Hercos, Guilherme Freitas de Lima (2023)
Chagas disease and human visceral leishmaniasis (HVL) are parasitic diseases caused by Trypanosoma cruzi (T. cruzi) and Leishmania infantum (L. infantum), respectively, both of the Trypanosomatidae protozoan family, considered by the World Health Organization as neglected tropical diseases. The drugs currently available to combat these diseases are: benznidazole for Chagas disease, however, it has a moderate efficiency in the acute phase of parasitosis, in addition to causing a series of side effects that lead in some cases to the abandonment of treatment by the victims; and amphotericin B for VLH, this drug has a certain efficiency in the treatment of this disease, but its acquisition is expensive, in addition to being toxic to human health. Given this context, it is necessary to develop new drugs, more efficient, less toxic and low cost for the treatment of these pathologies. In this work, the design, synthesis and study of the relationship between the chemical structure and biological activity of 23 compounds of a series of potent benzenesulfonamides against parasites of the Trypanosomatidae family were described. This project started from the planning of the modifications of a hit of the sulfonamide class, where it was established that the amino-aryl and benzenesulfonyl fragments of the hit would be modified. In the amino-aryl fragment, modifications were made in the positions of the substituent of the aromatic ring, the exchange of the amino group for other functional groups. Derivatives as above were performed with the addition of the carbonyl between the piperazine and the aromatic ring of this fragment. In the benzenesulfonyl fragment, modifications were made to the substituents attached to the aromatic ring. With the synthesized and characterized compounds, they were tested to verify the biological activity in vitro against the amastigote form of T. cruzi and L. infantum in cell culture. Of the modifications of the amino-aryl fragment, the most potent compound against T. cruzi was 4b (IC50 T. cruzi = 7.1 ± 4.8 µM; IS = 71.17) and against L. infantum was 7 (IC50 L. infantum = 0.90 µM; IS = >2457.7). From the series of modifications of the benzenesulfonyl fragment the most potent compound against T. cruzi was 11g (IC50 T. cruzi = 1.70 ± 0.09 µM; IS = 177) and against L. infantum was 11a (IC50 L. infantum = 6.06 ± 1.69 µM; IS = 404.7). The results obtained so far are of great value for the study of the relationship between chemical structure and biological activity, and are promising in the search for new drug candidates against Chagas disease and human visceral leishmaniasis.